MUTU PEMBELAJARAN DENGAN SISTEM DISTANCE LEARNING DIMASA PANDEMI COVID-19 - Enny Nurcahyawati Prasojo (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2020)
Abstract; Building an educated, intelligent society, like it or not, we have to change the paradigm in the learning system. A learning system is needed that can accommodate the aspirations of all groups of society. The quality of distance learning methods (Distence Learning) is often echoed when learning specializes in independence. In this case the educator does not need to convey material in one room. The innovation step in using network technology and information technology for the development of learning systems in higher education is the online lecture system. This type of learning can be carried out at the same time or at different times. With the PJJ (Distence Learning) system, it becomes flexible for students to study wherever they are. This makes it possible to match education with responsibility and commitment in all matters. Provide opportunities for students who are unable to learn due to limitations in distance, time, cost, and age.Keywords: Quality of learning, Distance Learning